Effect of pickling time on adhesion strength of ti oxide interlayer prior to diamond coating - Low, Yik Kuan, 1986-; Izman Sudin; Fakulti Kejuruteraan Mekanikal (2010)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Pembuatan)) - Universiti Teknologi Malaysia, 2010